ELECTROPOLYMERISATION AND CHARACTERISATION OF DOPED-POLYPYRROLE AS HUMIDITY SENSOR - Siswoyo Siswoyo; Trio F. Nugroho; Zulfikar Zulfikar; Agus Subekti (Indonesian Journal of Chemistry, 2006)
A new type of sensing materials for humidity measurement has been developed based on conducting polymer polypyrrole synthesised from pyrrole by adding some dopant compounds, bromide and chloride, it is prepared by potentiodynamic-electropolymerisation technique. Variation of dopant types and concentration has been carried out in order to investigate the effect of this variation to the change of polymeric conductivity when interacting with water vapour. Polypyrrole-Cl (Ppy-Cl) and polypyrrole-Br (Ppy-Br) exhibit a good principal characteristic as sensor candidate namely responding proportionally to humidly variation ranging 30% - 90% relative humidity. Characterisation test for the sensor candidates has been carried out for evaluating their linearity respond toward humidity, their stability in certain period and their reproducibility in some tests. The results show that Ppy-Cl and Ppy-Br showing good linearity respond with R value in a range of 0.95 - 0.99. Their reproducibility and sensitivity were relatively good, however their respond stability were only last in few days. The stability probably is related to the stability of resulted polymeric structure that very affected by synthesis process and dopant used. It is necessary to extend the use of other dopant materials and changing the synthesis process in order to improve sensor stability. In other hand it is also necessary to characterise other performance characteristic of the sensor namely response time, and interference effect of some volatile chemicals and other gases.